PENGEMBANGAN BAHAN AJAR IPAS BERBASIS KOMIK PADA MATERI MARI KENALI HEWAN DI SEKITAR KITA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III UPTD SDI BERTINGKAT KELAPA LIMA 1 KOTA KUPANG - Sine, Camelia; E Noya Nahak, Kristina; Bodkova Koli, Radka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in the IPAS subject on the topic “Let’s Get to Know Animals Around Us” in Grade III of UPTD SDI Bertingkat Kelapa Lima 1 Kupang City. The problem was caused by the use of less attractive teaching materials, inadequate presentation of the material, and students’ low reading interest during the learning process. This study aimed to determine the feasibility, practicality, and effectiveness of comic-based IPAS teaching materials in improving student learning outcomes. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 26 third-grade students of UPTD SDI Bertingkat Kelapa Lima 1 Kupang City. Data were collected through observation, interviews, questionnaires, and learning outcome tests. Data analysis techniques included quantitative descriptive analysis, normality tests, paired sample t-tests, and N-Gain tests. The results showed that the developed comic-based IPAS teaching materials were highly feasible based on the validation results of material experts (97%), media experts (97%), and language experts (95%). The practicality of the teaching materials was categorized as very good based on teacher responses (91.25%) and student responses (94.42%). Furthermore, the comic-based teaching materials were proven effective in improving student learning outcomes, as indicated by the increase in the average pretest score from 41.85 to the average posttest score of 89.73, with an N-Gain score of 81.96 categorized as high. The hypothesis testing result showed a significance value of 0.000 < 0.05, indicating a significant improvement in student learning outcomes after the use of comic-based teaching materials.